STUDY OF EFFECT Al2O3 NANOPARTICLES ON ELECTRICAL PROPERTIES OF EPOXY REINFORCEMENT BY CARBON FIBERS HYBRID COMPOSITES - Khdair, W. Y.; Salman, S. A.; Khdair, Z. T. (International Journal of Research -GRANTHAALAYAH, 2019)
In this paper was investigation the electrical properties of the epoxy "Hybrid Composites" as a function of a frequency. The composites constituents were epoxy using a matrix with reinforcement ratio (1:3) and volume fractions as (25% wt). The "Hybrid Composite" samples were prepared by addition alumina nanoparticles on the epoxy composites reinforced by carbon fibers with different volume fractions (0.1,0.3,0.5,0.7)w% by "Hand Lay-Up Molding". The experiments were performed to measure the electrical properties "Dielectric Constant, Dissipation Factor and Electrical Conductivity" in frequency range (10Hz-1MHz). The study showed that the reinforcement process resulted in an increase in the dielectric constant values of all manufactured models, and the addition of alumina nanoparticles leads to a decrease in the values of both the dielectric constant and the dielectric loss factor with increasing frequency and for all samples and for all values listed. Alternating electrical conductivity values increase significantly with increasing frequency and for all samples when alumina nanoparticles are added.